FORMATION OF READINESS OF FUTURE PRIMARY SCHOOL TEACHERS FOR ENVIRONMENTAL ACTIVITIES: CREATIVE ASPECT - Stakhova, Inna; Shikirinska, Olexandra; Demchenko, Olena; Groshovenko, Olga; Imber, Viktoriia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article actualizes the issue of forming the readiness of students pedagogical university to environmental activities. Based on the world and domestic environmental documents, new creative educational directions of ecological content in higher pedagogical institutions are determined. We conducted a definitive analysis of main concepts of the study: «creativity», «environmental activities», «readiness» and proposed its own definition of the term «readiness for environmental activities» (protecting, preserving and restoring the natural potential of nature). We have carried out a historical review of the main creative waysof formation teachers readiness for environmental activities. The aim of the article is to prove the effectiveness of the formation of the readiness of students for environmental activities through creative methodological exercises. We have proposed a system of creative exercises and tasks that must be used in the complex «classroom work – extracurricular work – independent training». Creative exercises allow to expand the panorama of ecological thinking of students, to acquire the necessary knowledge through analysis and personal appropriation, to enrich one own methodical stock with original, non-standard tasks of natural and ecological subjects. We have revealed the specifics of the introduction of a system creative exercises of environmental content for future teachers of rimary school. During the study we identified the criteria, indicators and levels (low, average, high) of readiness for environmental protection of future teachers, conducted a study on the basis of Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University, (Ukraine), and Kamianets-Podilskyi National Ivan Ohiienko University (Ukraine). We conducted an experimental study and found that the average level of readiness to environmental activities of future primary school teachers are vails in both universities, but Vinnytsia institute of high pedagogical education is the leader of high level, because students used a system of creative exercises in the educational process.